Effect of extremely low frequency electromagnetic fields on bacterial membrane - GARİP, GÜNSELİ AYŞE; AKSU, MEHMET BURAK (TAYLOR & FRANCIS LTD, 2016)
Purpose: The effect of extremely low frequency electromagnetic fields (ELF-EMF) on bacteria has attracted attention due to its potential for beneficial uses. This research aimed to determine the effect of ELF-EMF on bacterial membrane namely the membrane potential, surface potential, hydrophobicity, respiratory activity and growth.Materials and methods: Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli were subjected to ELF-EMF, 50Hz, 1mT for 2h. Membrane potential was determined by fluorescence spectroscopy with or without EDTA (Ethylenediaminetetraacetic acid) with DisC3(5) (3,3-dipropylthiacarbocyanine iodide), zeta potential measurements were performed by electrophoretic mobility, hydrophobicity of the membrane was measured with MATH (Microbial Adhesion to Hydrocarbons) test, respiratory activity was determined with CTC (5-Cyano-2,3-ditolyl tetrazolium chloride), colony forming unit (CFU) and DAPI (4,6-diamidino-2-phenylindole, dihydrochloride) was used for growth determinations.Results: ELF-EMF caused changes in physicochemical properties of both Gram-positive and Gram-negative bacteria. Hyperpolarization was seen in S. aureus and EDTA-treated E. coli. Surface potential showed a positive shift in S. aureus contrariwise to the negative shift seen in EDTA-untreated E. coli. Respiratory activity increased in both bacteria. A slight decrease in growth was observed.Conclusion: These results show that ELF-EMF affects the crucial physicochemical processes in both Gram-positive and Gram-negative bacteria which need further research.
Keywords: ELF-EMF; bacterial membrane potential; surface potential; bacterial hydrophobicity; respiratory activity; bacterial growth; ESCHERICHIA-COLI-CELLS; ELF MAGNETIC-FIELDS; BIOSYNTHETIC REQUIREMENTS; ELECTRIC-FIELDS; EXPOSURE; SURFACE; INHIBITION; REPAIR; DAMAGE; GROEL